WOMEN AND POLITICS: STRATEGIES IN OPTIMIZING WOMEN'S REPRESENTATION IN BANTEN PROVINCE LEGISLATIVE ELECTION POLITICS 2024 - Muhammad Asmawi; Lathifah Sandra Devi (JHR (Jurnal Hukum Replik), 2023)
Gender equality is still considered taboo in Indonesia. The stigma that women are weak, unable to lead or even interfere in politics is still widely heard in the general public. However, this stigma can be broken with Law number 22 of 2007 concerning Election Organizers which regulates the composition of the election implementation by paying attention to the representation of women at least 30%, in other words, the representation of women in politics has been legalized in law. The reality is that in fulfilling this quota, especially in Banten Province, it has not been filled to the fullest. The purpose of this writing is to optimize women's representation in the politics of legislative elections for 2024. The research approach uses a qualitative deductive with a qualitative descriptive method by trying to describe the phenomenon of strategies for optimizing women's representation in politics, judging from the facts on the ground that the 2019 legislative elections in Banten Province have not met the quota of 30 %. The results of the study obtained several strategies, namely inviting women to participate in the political arena, outreach and political education for women, improving the quality of women's resources and the role of the mass media to support and strengthen women's political participation in the public sphere.Keyword: Women's Representation, Politics, Legislative Elections